Pesan Perdamaian dalam Teks-Teks Keagamaan: Studi Komparatif atas Pemikiran Abdullah Saeed dan Omid Safi - Muhammad Zainul Arifin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
In the contemporary global context, discourse on religious texts and messages of peace has become increasingly crucial. Conflicts, radicalism, and identity tensions demand a deeper understanding of the peace-oriented values within sacred texts. The Qur’an, as the primary Islamic scripture, contains fundamental principles of justice, mercy, and social harmony. Interpretation of these messages largely depends on the hermeneutical approach employed. This study examines the messages of peace from the perspectives of two contemporary Muslim thinkers, Abdullah Saeed and Omid Safi, who use different yet complementary approaches. The study aims to answer: What are the messages of peace according to Abdullah Saeed and Omid Safi? What are the similarities and differences in their analyses? Through hermeneutics, Abdullah Saeed emphasizes historical context, contemporary realities, and the objectives of Sharia (maqasid al-shari‘ah), while Omid Safi emphasizes ethics of love and justice centered on spiritual experience. The study demonstrates that both scholars affirm the Qur’an as a living text guiding global society towards justice, inclusivity, and peace.